The mechanisms and diagnostic potential of lncRNAs, miRNAs, and their related signaling pathways in cervical cancer - Yan Xu; Yu Sun; Xiaobin Song; Jian Ren (Frontiers in Cell and Developmental Biology, 2023)
Cervical cancer (CC), the fourth most prevalent type of cancer among women worldwide, is associated with high rates of morbidity and mortality. Due to the long period of latency in CC, most patients are already in the middle to late stages when initially diagnosed, which greatly reduces the clinical cure rate and quality of survival, thus resulting in poor outcomes. In recent years, with continuous exploration in the fields of bioinformatics and molecules, it has been found that ncRNAs, including miRNAs and lncRNAs, without the ability to translate proteins are capable of activating or inhibiting certain signaling pathways by targeting and modulating the level of expression of proteins involved in these signaling pathways. ncRNAs play important roles in assisting with diagnosis, drug administration, and prediction of prognosis during CC progression. As an entry point, the mechanisms of interaction between miRNAs, lncRNAs, and signaling pathways have long been a focus in basic research relating to CC, and numerous experimental studies have confirmed the close relationship of miRNAs, lncRNAs, and signaling pathways with CC development. Against this background, we summarize the latest advances in the involvement of lncRNA- and miRNA-related signaling pathways in the development of CC to provide guidance for CC treatment.